2016
DOI: 10.5007/1980-0037.2016v18n3p322
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of changes in indirect markers of muscle damage responses following a 130-km cycling race

Abstract: DOI: http://dx.doi.org/10.5007/1980-0037.2016v18n3p322 The purpose of the present investigation was to identify the effects of a 130-km cycling race on indices of biochemical indirect markers of muscle damage and muscle soreness responses during a 72-hour recovery period. Fifteen endurance-trained male cyclists which were competing for more than 2 years and were involved in systematic training at least of 3 days/wk underwent a collection of indirect biochemical markers of muscle damage (CK, LDH, Myo) and delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…For instance, serum MYO concentration increases immediately after exercise and peak values are normally obtained within 24 h after exercise [55]. In contrast, the increase of CK is slower with peak values usually reached between 24 h and 96 h after exercise [56]. In addition, the pre-to post-race change is usually higher in MYO than in CK, suggesting that MYO might be considered a more specific biomarker of muscle damage when measured after endurance running events [49].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, serum MYO concentration increases immediately after exercise and peak values are normally obtained within 24 h after exercise [55]. In contrast, the increase of CK is slower with peak values usually reached between 24 h and 96 h after exercise [56]. In addition, the pre-to post-race change is usually higher in MYO than in CK, suggesting that MYO might be considered a more specific biomarker of muscle damage when measured after endurance running events [49].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it is observed to reach its maximum level at the 72nd hour. Similarly, LDH plasma levels following a 130°km cycling race increases and may remain elevated for up to 72 h in trained cyclists [36]. Peak torque deficits are most pronounced 24-48 h following DOMS-inducing exercise.…”
Section: Discussionmentioning
confidence: 96%
“…The present meta analysis evaluated indirect muscle damage indices, including CK and LDH among trained and untrained both sexes individuals, looking at reported articles. Proteins like CK and LDH have been extensively applied as markers of muscle micro-damages (45) and usually has been evaluated to be an indirect biomarkers of post exercise muscle damage due to their easiness of identification and the relatively low cost of tests to quantify it (46,47). In spite of CK and LDH rising post exercise being much variable and affected by exercise variable and individual factors, the assessment of CK and LDH pre-and post-exercise may provide a diagnostic tool for the detection of post-exercise muscle damage, with much less invasiveness than needed in a muscle biopsy (48).…”
Section: Discussionmentioning
confidence: 99%